2016
DOI: 10.1007/s00249-016-1132-3
|View full text |Cite
|
Sign up to set email alerts
|

Differential stability of DNA based on salt concentration

Abstract: Intracellular positive ions neutralize negative charges on the phosphates of a DNA strand, conferring greater strength on the hydrogen bonds that connect complementary strands into a double helix and so confer enhanced stability. Beyond a certain value of salt concentration, the DNA molecule displays an unstable nature in vivo as well as in vitro. We consider a wide range of salt concentrations and study the stability of the DNA double helix using a statistical model. Through numerical calculations, we attempt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 60 publications
0
19
0
Order By: Relevance
“…The high-salt condition is also known to compromise the double helical structure and lead to partial denaturation of dsDNA. 59 This change of structural integrity was then reflected in the alkyne-HDX speed-up for both EdU-labeled dsDNA and cellular DNA. Collectively, our results for different DNA species under varied conditions establish the viability of employing alkyne-HDX to sense and study the local DNA environments.…”
Section: ■ Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…The high-salt condition is also known to compromise the double helical structure and lead to partial denaturation of dsDNA. 59 This change of structural integrity was then reflected in the alkyne-HDX speed-up for both EdU-labeled dsDNA and cellular DNA. Collectively, our results for different DNA species under varied conditions establish the viability of employing alkyne-HDX to sense and study the local DNA environments.…”
Section: ■ Resultsmentioning
confidence: 85%
“…This result implies that our alkyne-HDX strategy is indeed sensitive to the change of DNA structures. To gain more insights into the causes of varying alkyne-HDX kinetics across different EdU-labeled DNA structures, we next investigated how the high-salt condition (DPBS-D 2 O buffer with 2 M NaCl), which could perturb the DNA electrostatic interactions, modulates the alkyne-HDX of EdU (Figure e, light blue bars). We confirmed that the high osmolarity would not alter the D 2 O diffusion rate across cells by both spontaneous Raman and SRS measurements (Figure S3d–f).…”
Section: Resultsmentioning
confidence: 99%
“…By evaluating the partition function, we calculate free energy per base pair hence specific heat as a function of temperature. The melting temperature T m of chain at various angular separations(θ) for conical confined geometry and in different diameter of the cylinder for cylindrical confined geometry are calculated through the peak in specific heat as a function of temperature [2,57]. The results are plotted in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…If the solutions are allowed to dry on the fused silica substrate upon which the bowtie antennas are mounted, then buffer solutions become concentrated, leading to DNA denaturation under high salt conditions (48)(49)(50). This occurs for both m-and n-types of DNA.…”
Section: Denaturationmentioning
confidence: 99%